Irrational Economic Decision-Making after Ventromedial Prefrontal Damage: Evidence from the Ultimatum Game - Koenigs, Michael; Tranel, Daniel (The Journal of neuroscience, 2007)
Emotion regulation is often critical for adaptive decision making. Here, we investigate whether emotion regulation defects following focal prefrontal brain damage are associated with exceptionally irrational economic decision making in situations of unfair treatment. In the Ultimatum Game, two players are given one opportunity to split a sum of money. One player (the proposer) offers a portion of the money to the second player (the responder) and keeps the rest. The responder can either accept the offer (in which case both players split the money as proposed) or reject the offer (in which case both players get nothing). Relatively low Ultimatum offers are often rejected, and this “irrational” behavior has been attributed to an emotional reaction to unfair treatment. Using the lesion method, we tested the hypothesis that damage to ventromedial prefrontal cortex (VMPC), an area critical for the modulation of emotional reactions, would result in exaggerated irrational economic decisions. Subjects acted as the responder to 22 different proposers who offered various splits of $10. Offers ranged from fair (give $5, keep $5) to extremely unfair (give $1, keep $9). The rejection rate of the VMPC group was higher than the rejection rates of the comparison groups for each of the most unfair offers ($7/$3, $8/$2, $9/$1). These results suggest that emotion regulation processes subserved by VMPC are a critical component of normal economic decision making.